Treatment of peritoneal carcinomatosis with hyperthermic intraperitoneal chemotherapy in colorectal cancer. Issue 9 (30th June 2017) - Behrenbruch, Corina; Hollande, Frédéric; Thomson, Benjamin; Michael, Michael; Warrier, Satish K.; Lynch, Craig; Heriot, Alexander
Abstract : The peritoneum is the second most common site of metastasis after the liver and the only site of metastatic disease in approximately 25% of patients with colorectal cancer (CRC). In the past, peritoneal carcinomatosis in CRC was thought to be equivalent to distant metastasis; however, the transcoelomic spread of malignant cells is an acknowledged alternative pathway. Metastasectomy with curative intent is well accepted in patients with liver metastasis in CRC despite the paucity of randomized trials. Therefore, there is rationale for local treatment with peritonectomy to eliminate macroscopic disease, followed by hyperthermic intraperitoneal chemotherapy to destroy any residual free tumour cells within the peritoneal cavity. The aim of this paper is to summarize the current evidence for cytoreduction and hyperthermic intraperitoneal chemotherapy in the treatment of peritoneal carcinomatosis in CRC.